IMPLEMENTATION OF THE ASSIMILATION AND EDUCATION (SAE) PROGRAM ON RESIDENTIAL PREVENTION IN THE CLASS IIA CORRECTIONS INSTITUTION KEDIRI - Ardianto, Muhammad Alrian Tri; Simanjuntak, Meitisa Vanya (Journal of Management Small and Medium Enterprises (SMEs), 2025)
This research discusses the implementation of the Assimilation and Education Facilities (SAE) program on the prevention of recidivism at the Class IIA Kediri Correctional Institution. This study aims to analyze and find out the obstacles in the implementation of the SAE program on the prevention of recidivists at the Class IIA Kediri Correctional Institution. The method used is a qualitative method, data collection techniques such as observation, interviews, and document studies. The results of this study are that the program carried out in the implementation of SAE at Class IIA Kediri Correctional Institution has been running well, the implementing organization understands the challenges faced so that prisoners have responsibility and understand the importance of working, and the target of the SAE program for program socialization has been carried out well. However, in this implementation there are obstacles such as obsolete equipment facilities and the availability of late provision of activity materials. Keywords: Implementation; Assimilation and Education Facilities Program; Recidivism